What Happened at Nong Sarai? Comparing Indigenous and European Sources for Late 16th Century Siam - Terwiel, Barend Jan (The Journal of the Siam Society, 2013)
The elephant duel in 1593 at Nong Sarai between Naresuan and the Burmese crown prince is one of the most famous incidents in Thai history, often repeated in a standard version. In fact, there are (at least) ten different accounts of the battle that differ widely. Comparing these accounts by Siamese, Burmese, European and Persian authors throws insight both on what may have truly happened at Nong Sarai and on the writing of Thai history.